The Effect of Grooming on Five Commercial Antifouling Coatings - Ralston, Emily; Gardner, Harrison; Hunsucker, Kelli Zargiel; Swain, Geoffrey (Frontiers in Marine Science, 2022)
The majority of ships are coated with antifouling paint. These coatings can fail to completely protect from fouling due to mismatches between paint type and duty cycle, the presence of biocide tolerant fouling organisms, improperly applied, old or damaged paint, etc. Grooming antifouling coatings can provide a solution. Five commercially available antifouling coatings were applied to panels. Half of the replicates were groomed weekly, the other half were immersed and allowed to freely foul, undisturbed. Photographs were taken and panels were visually assessed monthly. Over the period of two years, all the undisturbed panels became fouled with a diverse community of macrofouling organisms including encrusting and arborescent bryozoans, barnacles, tube worms, oysters, tunicates and more. The groomed panels remained clean of macrofouling for an extended period of time, up to two years depending on the coating. Cover of biofilm was also low on groomed panels. Grooming was effective at maintaining different antifouling paints clear of macrofouling and decreasing cover of biofilms for up to two years of immersion.